Pengaruh Metode Pembelajaran Terhadap Prestasi Belajar Siswa di SMP Swasta Muhammadiyah 48 Medan - Nurmaini, Ella; Pras, Jogi; Nasution, Abdul Fattah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the impact of lecture, discussion, and project-based learning methods on students' academic achievement at SMP Swasta Muhammadiyah 48 Medan. Using a quantitative approach and quasi-experimental method, the research involved 40 eighth-grade students divided into experimental and control groups. Data were collected through pre-test and post-test evaluations and analyzed using ANOVA. The results show that the discussion method significantly improves students' academic performance compared to lecture and project-based learning methods. The lecture method was found to be less effective, while project-based learning positively influenced students' practical skills. This study recommends using varied teaching methods to optimize students' learning outcomes.